2018
DOI: 10.1055/s-0039-1688801
|View full text |Cite
|
Sign up to set email alerts
|

Oocyte and Embryo Manipulation and Epigenetics

Abstract: Regulation of the epigenome is a mechanism by which the environment influences gene expression and consequently the health of the individual. The advent and refinement of novel assisted reproductive technology (ART) laboratory techniques, including vitrification, dynamic culture systems, oocyte in vitro maturation, laser-assisted hatching, intracytoplasmic sperm injection, and preimplantation genetic testing for aneuploidy have contributed to the success of ART. From fertilization through implantation, the epi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 84 publications
0
14
0
1
Order By: Relevance
“…As the use of assisted reproductive technologies (ART) procedures becomes more common, its effect on epigenetic regulation of embryonic development needs to be examined. It has been shown that ART procedures cause a high level of chromosomal abnormalities including aneuploidies, chromosomal breaks, rearrangements which can lead to CNVs, and epigenetic changes (51). Furthermore, due to the timing of ART, which is performed during major epigenetic remodeling in the early embryo, inappropriate gene silencing or activation could result in CAKUT or other defects.…”
Section: Epigenetic Changes: How the Environment Affects Gene Expressionmentioning
confidence: 99%
“…As the use of assisted reproductive technologies (ART) procedures becomes more common, its effect on epigenetic regulation of embryonic development needs to be examined. It has been shown that ART procedures cause a high level of chromosomal abnormalities including aneuploidies, chromosomal breaks, rearrangements which can lead to CNVs, and epigenetic changes (51). Furthermore, due to the timing of ART, which is performed during major epigenetic remodeling in the early embryo, inappropriate gene silencing or activation could result in CAKUT or other defects.…”
Section: Epigenetic Changes: How the Environment Affects Gene Expressionmentioning
confidence: 99%
“…There is also no transcription of the zygote genome at the early stages of embryo development, which begins at fertilization when a haploid oocyte fuses with a sperm. Although the maternal and paternal gametes offer equal genetic materials, early embryo development mainly depends on maternal mRNAs and proteins in the oocyte ( Osman et al, 2018 ). These proteins are mainly activated during fertilization and the maternal-to-zygotic transition ( Yartseva and Giraldez, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Due to the inability to conduct in vitro spermatogenesis in livestock species, sperm usually experience less environmental stressors than oocytes. For example, stresses during IVM, including oxygen tension, temperature fluctuation, media composition and osmotic stress, could cause epigenetic alternations in oocytes (El Hajj and Haaf, 2013;Osman et al, 2018). In domestic species, since the establishment of epigenetic modifications has finished before sperm are retrieved and treated for IVP, the chance is much higher that epigenetic defects in the sperm genome come from perturbation during in vivo spermatogenesis rather than sperm handling procedures (Urrego et al, 2014).…”
Section: Epigenetic Modifications Associated With Sperm Fertility In mentioning
confidence: 99%